Evaluation of an online human-robot interaction competition platform based on virtual reality – case study in RCAP2021. (18th April 2023) - Mizuchi, Yoshiaki; Yamada, Hiroki; Inamura, Tetsunari
Abstract : Due to the COVID-19 pandemic, many robot competitions have been canceled in the past years. To address this problem, we proposed a cloud-based VR platform for the crowdsourcing of embodied human-robot interactions. However, this system only suggested the feasibility of the competition application, and actual competitions had not yet been held and implemented. Therefore, through demonstration experiments in the RoboCup Asia Pacific (RCAP) conducted in a hybrid format with on-site and remote participation, we evaluated the usefulness of using cloud computing on AWS from whether the latency time causes problems in human-robot interaction in a virtual reality environment. GRAPHICAL ABSTRACT: UF0001